The factors influencing employee motivation in Felda / Mohd Farid Abu Bakar and Nor Haziyah Mamat - Abu Bakar, Mohd Farid; Mamat, Nor Haziyah (Faculty of Business and Management, 2013)
Employee motivation becomes important for organization to survive. To engage in the practice of motivating employees, employers must understand the unsatisfied needs of each of the employee groups. It is because different employees usually have different types of needs. Besides that, employee motivation also helps the organizations to survive. Motivated employees are more productive. Thus to be effective, managers need to understand what motivates employee within the context of the functions & roles they perform. This research study on three dimensions that influence employee motivation which are compensation, work environment and career development. The researchers need to find out what are the relationship these three dimension with employee motivation and which one of these factor that most significant to employee motivation among employee in Felda. Besides that, the researchers also want to determine the level of employee motivation in Felda. This study has conducted in Wisma Felda on 100 respondents to be sample and used questionnaires to collect the data. The findings of this study indicate career development is the most factors that influencing employee motivation in the organization. Based on the findings the researchers have come up with several type of recommendation to be taken as an action by Felda which is first, Felda Senior Leader in Felda should make career development as a priority if they want to increase their employee motivation. Next, Felda can send their Line Manager to a better training by provide a tools and skills for supporting their career development. Lastly Felda can combine individualized coaching and group session.